Unsteady Simulation of a Synthetic Jet Actuator with Cylindrical Cavity Using a 3-D Lattice Boltzmann Method - Hongbin Mu; Qingdong Yan; Wei Wei; Pierre E. Sullivan (International Journal of Aerospace Engineering)
A synthetic jet actuator is a zero-net mass-flux device that imparts momentum to its surroundings and has proved to be a useful active flow control device. Using the lattice Boltzmann method (LBM) with the Bhatnagar-Gross-Krook (BGK) collision models, a 3-D simulation of a synthetic jet with cylindrical cavity employing a sinusoidal velocity inlet boundary condition was conducted. The velocity distributions are illustrated and discussed, and the numerical results are validated against previous experimental data. The computed results show the ingestion and expulsion flow over one working cycle as well as the evolution of vortices important to the control of the separated shear layer. Zero-net mass-flux behavior is confirmed.